Multibody system dynamic analysis and payload swing control of tower crane. (September 2022) - Li, Kun; Liu, Manlan; Yu, Zuqing; Lan, Peng; Lu, Nianli
A new payload swing control method considering the vibration of tower crane is proposed in this study. The coupling between the structural vibration and the payload swing is neglected in existing studies on tower crane swing suppression. Changes of sling length are considered as disturbances. They cause the existing methods of swing suppression method ineffectual in the actual working situation. In contrast, the structural vibration of the tower crane is taken into account in this study. At the same time, the sling length is regarded as a control variable to reduce the payload swing. A new swing suppression algorithm is proposed in conjunction with phase plane analysis method. In addition, a systematical tower crane multibody system dynamic analysis platform with changing of sling length is established to verify the effectiveness of the algorithm. The traditional finite element method is used to model the tower body and boom of tower crane while the Arbitrary Lagrange Euler Absolute Nodal Coordinate Formulation (ALE-ANCF) cable element is applied for modeling the sling. This two parts are connected with sliding joint obtaining the tower crane multibody system model. Numerical examples show that the proposed method can reduce the swing amplitude the payload effectively when considering the coupling between the structural vibration and the payload swing.